Analisis Perilaku Cyberloafing (Browsing Medsos Jam Kerja) Pada Gen Z: Dampaknya Terhadap Kreativitas Dan Produktivitas - Nur Khaila Anugra Maryam; Agus Halim (CV. SINAR HOWUHOWU, 2026)
The development of digital technology and the high penetration of social media have given rise to various changes in work behavior, particularly among Generation Z as the digital native generation. One phenomenon commonly found in the modern workplace is cyberloafing, which is the activity of using the internet for personal purposes during work hours, such as browsing social media. This phenomenon is often perceived as negative behavior because it is considered to reduce work productivity, but on the other hand, it is also considered to have the potential to increase employee creativity. This article aims to analyze cyberloafing behavior in Generation Z and its impact on creativity and work productivity. This study uses a qualitative approach with a literature study method (indirect research) through a systematic review of books, journal articles, and relevant scientific publications. The results of the study indicate that cyberloafing has an ambivalent impact, namely the potential to reduce productivity if done excessively, but can increase creativity when done within reasonable limits as a means of cognitive relaxation. The conclusion of this study confirms that cyberloafing cannot be viewed solely as dysfunctional behavior, but rather requires adaptive management. Further research is recommended to test these conceptual findings empirically in various organizational contexts.